Pendugaan Waktu Kedaluwarsa Pendistribusian Manisan Salak Menggunakan Metode Q10 - Ida Ayu Mas Oceanic; Ida Bagus Putu Gunadnya; I Wayan Widia (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This study aimed to determine the change of quality parameters, to determine the critical quality parameter and to predict the distribution expired time of snake fruit candy using Q10 method. Snake fruit candy was stored at three different storage temperatures, namely 35, 45 and 55oC for 20 hours. Each storage room was loaded with 126 candies and observation was done every 4 hour on parameters of texture, aroma, color and flavor of the candy. The results showed that the longer the storage, the value of candy texture increased from an average of 7,06 N to 250,20 N. Meanwhile, the score of aroma of candy decreased from an average of 4,13 to 1,00. The score of color also decreased from an average of 4,93 to 1,00. The same phenomenon was also observed on flavor of candy which decreased from an average of 4,67 to 1,00. The critical quality parameter of the snake fruit candy was flavor which followed the first reaction order. The Q10 of the flavor deterioration was determined at the basic temperature of 45oC and it was found its value was 1,94. By using Q10, it was predicted that distribution expired time of snake fruit candy stored at temperature distribution of 15, 25, 35, 45, and 55oC was 220 hours (9,19 days), 114 hours (4,73 days), 58 hours (2,44 days), 30 hours (1,25 days), and 15 hours (0,65 day), respectively.